Hak Nafkah Anak Luar Nikah - M abdillah alkamil (Taruna Law: Journal of Law and Syariah, 2025)
The status of illegitimate children in obtaining their rights, such as the right to support that they should receive, is often an issue that is frequently discussed. Illegitimate children include children born as a result of a marriage that is legally valid but not registered or what is usually called an unregistered marriage. In positive law, illegitimate children only have a civil relationship with their mother and her mother's family. So it is difficult for the child to get his rights. After the Constitutional Court Decision No. 46/PUU-VIII/2010 appeared, which stated that the status of an illegitimate child has a civil relationship with the father and the father's family as long as it can be proven based on science. The purpose of this writing is to examine the right to support illegitimate children in the decision, MK No. 46/PUU-VIII/2010, seen from the perspective of Islamic law. This research uses library research methods (library research). The results of this research show that illegitimate children still receive and are entitled to support from their father. Because if seen from an Islamic religious perspective, the marriage is religiously valid because it fulfills the requirements and pillars of marriage. So illegitimate children still have rights, such as support from both parents, which they must receive.